2005
DOI: 10.1002/cne.20410
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic morphology, local circuitry, and intrinsic electrophysiology of neurons in the rat medial and lateral habenular nuclei of the epithalamus

Abstract: The habenular complex of the epithalamus in the mammalian brain receives input from the limbic forebrain and pallidum and, in turn, projects to numerous midbrain structures. Traditionally, the habenular complex is divided into the medial nucleus and two divisions of the lateral nucleus. Based on their distinct input and output pathways, the habenula is considered to constitute three, partially overlapping channels that regulate information flow from the limbic forebrain and pallidum to the midbrain. As a step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
147
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(166 citation statements)
references
References 41 publications
(46 reference statements)
17
147
2
Order By: Relevance
“…Neurons in the dMHb exhibited slow, irregular spontaneous firing at baseline, consistent with prior reports of spontaneous habenula activity (Kim and Chang, 2005). Trains of blue light pulses elicited 1:1 spiking of action potentials from dMHb neurons at frequencies of up to 20 Hz (Fig.…”
Section: Activation Of the Dmhb Is Intrinsically Reinforcingsupporting
confidence: 89%
See 1 more Smart Citation
“…Neurons in the dMHb exhibited slow, irregular spontaneous firing at baseline, consistent with prior reports of spontaneous habenula activity (Kim and Chang, 2005). Trains of blue light pulses elicited 1:1 spiking of action potentials from dMHb neurons at frequencies of up to 20 Hz (Fig.…”
Section: Activation Of the Dmhb Is Intrinsically Reinforcingsupporting
confidence: 89%
“…MHb neurons exhibit irregular spontaneous firing (Kim and Chang, 2005) and thus provide continuous excitatory input to the IP. If the dMHb mediates primary reinforcement, inhibition of this tonic input would be predicted to be aversive.…”
Section: Inhibition Of Tonic Dmhb Output To the Ipl Is Aversivementioning
confidence: 99%
“…In addition, a very recent study in the zebrafish has shown the failure of neural activation of the dHb neurons after exposure to the AS and chondroitin sulfate (24). Therefore, the effect of AS on Kiss1 neurons could be modulated via signaling inside the habenula subnuclei (from dHb to vHb), similar to the rat habenula (25), or by other afferent pathways in the forebrain.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have begun to dissect the medial and lateral habenular nuclei in an effort to determine whether subpopulation differences in cytoarchitecture and connectivity could be correlated to molecular markers and electrophysiological properties (14)(15)(16)(17). For instance, the dorsal and ventral parts of the MHb can be clearly divided based on their respective enrichment in the neuropeptide Tachykinin 1, also known as substance P (SP), or the ACh synthesizing enzyme choline acetyltransferase (ChAT), and the segregation of their efferents to different parts of the IPN (18).…”
mentioning
confidence: 99%
“…A recent study showed that MHb ChAT-positive neurons corelease glutamate and ACh upon different patterns of blue-light stimulation in transgenic ChATChannelrhodopsin mice (19), but that sufficient ACh to activate nAChRs in IPN neurons is detected only once a certain threshold of tonic firing is reached. Given that it has been reported that medial habenular neurons generate tonic trains of action potentials (15), similar to neurons in the mesolimbic dopamine tract, we wanted to address whether this property was restricted to cholinergic neurons, and whether this tonic firing could be modulated in vivo by nicotine. Here, we analyzed the pacemaking activity and translating ribosome affinity purification (TRAP) molecular profile of MHb neurons.…”
mentioning
confidence: 99%